أصول التفكير الاصطلاحي الصوتي عند الفلاسفة المسلمين ومصادره ـ بحث في خلفية الإبداع والاتباع ـ (مجلة إحالات, 2025)
إنّ معرفة الفلاسفة الموسوعيّة و مُشاركتهم في أكثر من علم جعلت المعلومات الصّوتية متفرّقة ، كما أنّ عصر التخصّص حجبَ عنّا علمهم الصّوتي و جزّأ الحكم عليه و هذا البحث يجتهد في الكشف عن مسألة تعتبر الآن من أهمّ مسائل تأصيل تراثنا الفلسفي العربي و بوجه خاص دور الفلاسفة المسلمين في علم المصطلح الصوتي و إعمامه ونشره جادّة في الإجابة عن الأسئلة التالية: ـ هل استطاع الفلاسفة المسلمون إبداع مصطلحات صوتيّة خاصّة بهم ؟ ـ ما هي المنهجيّة التي استحوذت على تفكيرهم الصّوتي ؟ ـ هل مصطلحاتهم الصوتية امتداد لمصطلحات النحاة واللغويين العرب والأعاجم ؟ أم أنّ مصطلحاتهم الصّوتية لها سمات معيّنة تُميّزها عن غيرها ؟ تلك جملة الإشكاليات سأحرص على الإجابة عنها مستعينة بالمنهج الوصفي المناسب لطبيعة البحث .Abstract : The knowledge of the encyclopedic philosophers and their participation inmore than one science has made the audio information sparse, and the age of specialization has obscured our knowledge of the voice and part of the judgment and this research strives to uncover the issue is now one of the most important issues of the rooting of our Arab philosophical heritage and in particular the role of Muslim philosophers In the science of audio terminology and its dissemination and publication is serious in answering the following questions Can Muslim philosophers create their own idioms? What is the methodology that captured their voice thinking ? Are their phonetic terms an extension of the terminology of grammarians, linguists, and linguists? Or do their vocal terms have certain characteristics that distinguish them from others? These are all the problems I will be careful to answer using the descriptiveapproach appropriate to the nature of research.